Glucose derived carbon modified magnetic metal oxide catalyst as well as preparation method and application thereof

By modifying the magnetic metal oxide catalyst MnFe2O4@GC with glucose-derived carbon, the problems of high cost, insufficient active sites and difficult recovery of existing catalysts are solved, achieving low-cost, high-efficiency and environmentally friendly TC degradation, which is suitable for peracetic acid activation over a wide pH range.

CN121314604APending Publication Date: 2026-01-13NANCHANG INST OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511426572.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-30
Publication Date
2026-01-13

AI Technical Summary

Technical Problem

Existing catalysts for activating peracetic acid to degrade tetracycline suffer from problems such as high cost, insufficient exposure of active sites, difficulty in recovery, and narrow pH range. Traditional carbon materials are costly to prepare and have high potential toxicity, while biochar requires high-temperature pyrolysis, resulting in high energy consumption and uncontrollable pore structure.

Method used

The glucose-derived carbon-modified magnetic metal oxide catalyst MnFe2O4@GC was prepared by a one-step hydrothermal carbonization method. MnFe2O4 nanoparticles were loaded onto the glucose-derived carbon framework to form a uniformly dispersed composite material. The catalyst was rapidly recovered by using an external magnetic field and was efficiently activated to degrade TC in PAA over a wide pH range.

Benefits of technology

It achieves low-cost, environmentally friendly TC removal, the catalyst can be recycled multiple times, the TC removal rate reaches 98.1% within 30 minutes, it maintains high degradation performance within the pH range of 3.0-9.0, and the catalyst has good stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121314604A_ABST
    Figure CN121314604A_ABST
Patent Text Reader

Abstract

The invention discloses a glucose derived carbon modified magnetic metal oxide catalyst as well as a preparation method and application thereof. According to the catalyst, glucose is taken as a carbon source, spinel manganese ferrite MnFe2O4 nanoparticles are uniformly anchored on the surface of a porous carbon skeleton through a hydrothermal-calcination process, the saturation magnetization reaches 21.21 emu / g, and rapid separation can be realized in an external magnetic field within 5 seconds. The catalyst is applied to activation of peracetic acid PAA for oxidative degradation of tetracycline TC. The degradation reaction conditions are as follows: the TC initial concentration is 10 mg / L, the PAA concentration is 200 mu M, the catalyst addition amount is 0.1 g / L, the initial pH is 3.0-9.0, the reaction time is 30 minutes, and the TC removal rate is greater than or equal to 97%. The catalyst is cheap in raw materials, simple and convenient to prepare, magnetically recoverable, wide in pH adaptation and free of secondary pollution, and has large-scale preparation and engineering application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of environmental functional materials and advanced oxidation water treatment technology, specifically relating to a magnetic metal oxide / carbon composite catalyst prepared with glucose as a precursor and a method for activating peracetic acid (PAA) to degrade tetracycline (TC). Background Technology

[0002] Tetracycline (TC) is one of the most widely used broad-spectrum antibiotics. TC residues in the environment can induce the development of drug-resistant bacteria and resistance genes, posing a serious threat to ecological security and human health. Traditional biological and physicochemical methods are inefficient at removing low concentrations of recalcitrant TC from water bodies. Based on sulfate free radicals (SO4· ... - Advanced oxidation techniques (AOPs) using hydroxyl radicals (·OH) or hydroxyl radicals have attracted widespread attention due to their strong oxidizing power and fast reaction rate. Peracetic acid (PAA), as a novel oxidant, has advantages such as safe transportation and non-toxic decomposition products. Upon activation, it can produce CH3C(O)OO·, ·OH, and other compounds. 1 O2 and other bioactive species have become a research hotspot in recent years.

[0003] Currently, catalysts commonly used to activate PAA include homogeneous transition metal ions (Fe2+). 2+ Co 2+ Homogeneous systems (such as graphene, carbon nanotubes, and biochar) and heterogeneous metal oxides (such as Co3O4 and MnFe2O4) are also used to support metal oxides to improve catalytic activity and stability. However, homogeneous systems suffer from problems such as metal ion loss, narrow pH range, and secondary pollution; heterogeneous metal oxides suffer from defects such as easy aggregation, insufficient exposure of active sites, and difficulty in recovery. Carbon materials (such as graphene, carbon nanotubes, and biochar) are widely used to support metal oxides to improve catalytic activity and stability due to their large specific surface area, good conductivity, and rich surface functional groups. However, graphene and carbon nanotubes have high preparation costs and potential toxicity; traditional biochar requires high-temperature pyrolysis, which is energy-intensive and has an uncontrollable pore structure.

[0004] Glucose is an inexpensive, renewable, and environmentally friendly biomass that can be carbonized under mild hydrothermal conditions to form carbon materials rich in oxygen-containing functional groups such as -OH and -COOH. However, there are currently no research reports on using glucose-derived carbon (GC) as a support to support MnFe2O4 for activating PAA degradation of TC. Therefore, developing a low-cost, simple-to-prepare, environmentally friendly, and magnetically recoverable glucose-derived carbon-modified magnetic metal oxide catalyst is of great significance. Summary of the Invention

[0005] The purpose of this invention is to provide a glucose-derived carbon-modified magnetic metal oxide catalyst (MnFe2O4@GC) and its preparation method, to solve the problems of high catalyst cost, insufficient exposure of active sites, and difficulty in recovery in the prior art. Another purpose of this invention is to provide the application of this catalyst in the efficient degradation of TC by activated PAA, achieving rapid removal of TC over a wide pH range, and the catalyst can be recycled multiple times.

[0006] This invention is achieved through the following technical solution:

[0007] A method for preparing a glucose-derived carbon-modified magnetic metal oxide catalyst includes the following steps:

[0008] (1) Preparation of spinel manganese ferrite (MnFe2O4): The metal salts FeCl3·6H2O and MnCl2·4H2O were dissolved in ethylene glycol (EG). After they were completely dissolved, sodium acetate (NaAc) and polyethylene glycol (PEG) were added. After stirring thoroughly, the mixture was transferred to a reaction vessel for aging. The product was initially enriched by a magnet, and after washing with ethanol and water several times, it was dried under vacuum and then ground to obtain magnetic MnFe2O4.

[0009] (2) Preparation of glucose-modified magnetic metal oxide precursor: The MnFe2O4 nanoparticles prepared in step (1) were ultrasonically dispersed in deionized water, glucose (GC) was added, and after ultrasonic dispersion was continued to be uniform, the mixture was transferred to a reaction vessel for hydrothermal reaction; the product was initially enriched by a magnet, and after being washed several times with ethanol and water, it was dried under vacuum and then ground to obtain the glucose-modified magnetic metal oxide precursor.

[0010] (3) Preparation of glucose-derived carbon-modified magnetic metal oxide (MnFe2O4@GC): The glucose-modified magnetic metal oxide precursor prepared in step (2) was placed in a tube furnace and calcined to obtain MnFe2O4@GC.

[0011] In the above method, in step (1), the molar ratio of Fe:Mn is 5:1-2:1, the amounts of FeCl3·6H2O and MnCl2·4H2O are 2.703-6.758g and 0.990-1.980g, respectively; the amount of EG is 80-100mL, and the amounts of NaAc and PEG are 4.8-7.2g and 1.5-3.0g, respectively.

[0012] In the above method, in step (1), the reactor volume is 50-100 mL, the aging temperature is 180-200℃, and the aging time is 10-12 h; the vacuum drying temperature is 60-80℃, and the drying time is 16-20 h.

[0013] In the above method, in step (2), the mass ratio of MnFe2O4 to glucose is 1:5-2:5, and the amounts of MnFe2O4 and glucose are 0.4-1.6g and 2.0-4.0g, respectively; the amount of distilled water is 160-200mL.

[0014] In the above method, in step (2), the volume of the reaction vessel is 100-200mL, the hydrothermal reaction temperature is 180-200℃, the hydrothermal reaction time is 12-14h, the vacuum drying temperature is 60-80℃, and the drying time is 16-20h.

[0015] In the above method, in step (3), the heating rate of the tube furnace is 5-10℃ / min, the calcination temperature is 300-500℃, and the calcination time is 4-6h.

[0016] In the obtained MnFe2O4@GC composite catalyst, MnFe2O4 nanoparticles are uniformly supported on the surface of a glucose-derived carbon framework, with a saturation magnetization of 21.21 emu / g, which can be rapidly separated by an external magnetic field. Simultaneously, the MnFe2O4@GC composite catalyst contains abundant oxygen-containing functional groups and Fe... 2+ / Fe 3+ and Mn 3+ / Mn 2+ Both redox couples contribute to the activation of PAA and the removal of TC.

[0017] Furthermore, the above-mentioned composite catalyst was used in the oxidative degradation of tetracycline (TC) by activated peracetic acid (PAA).

[0018] Furthermore, the degradation reaction conditions were as follows: initial TC concentration 10 mg / L, PAA concentration 200 μM, catalyst dosage 0.1 g / L, initial pH 3.0-9.0, reaction time 30 min, and TC removal rate ≥97%.

[0019] Furthermore, after the composite catalyst is recycled 5 times, the TC removal rate is still ≥90%, demonstrating good stability and reusability.

[0020] Furthermore, the degradation mechanism involves free radicals (·OH, CH3C(O)OO·) and non-free radicals ( 1 The interaction of O2 and other substances, with CH3C(O)OO· being the main active species.

[0021] Furthermore, the coexisting anion Cl in water - HCO3 - SO4 2- It has no significant inhibitory effect on TC degradation; humic acid (HA) has a slight inhibitory effect on TC removal due to competition for active sites.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] 1. Raw materials are cheap and readily available: Glucose is a renewable biomass with a wide range of sources and a cost far lower than carbon materials such as graphene and carbon nanotubes;

[0024] 2. Simple preparation process: It adopts a one-step hydrothermal carbonization method, which does not require high-temperature pyrolysis, has low energy consumption, and is easy to scale up for production;

[0025] 3. Excellent catalytic performance: The MnFe2O4@GC / PAA system achieved a TC removal rate of 98.1% within 30 minutes, which is superior to similar catalysts;

[0026] 4. Environmentally friendly: The catalyst can be magnetically recovered, with no secondary pollution, and its activity remains almost unchanged after being recycled 5 times;

[0027] 5. Wide pH range: It maintains high degradation performance within the pH range of 3.0-9.0, and has broad prospects for practical application. Attached Figure Description

[0028] Figure 1 This is a scanning electron microscope image of MnFe2O4@GC.

[0029] Figure 2 These are the hysteresis loop and magnetic separation diagram of MnFe2O4@GC.

[0030] Figure 3 These are XPS images before and after the MnFe2O4@GC reaction. Detailed Implementation

[0031] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments:

[0032] Example 1

[0033] The preparation of a glucose-derived carbon-modified magnetic metal oxide catalyst includes the following steps:

[0034] (1) Preparation of spinel manganese ferrite MnFe2O4: 2.703g FeCl3·6H2O and 0.990g MnCl2·4H2O were dissolved in 80mL ethylene glycol EG. After they were completely dissolved, 7.2g sodium acetate NaAc and 3.0g polyethylene glycol PEG were added. After stirring thoroughly, the mixture was transferred to a 100mL reactor and aged at 200℃ for 10h. The product was initially enriched by a magnet and washed several times with ethanol and water. After vacuum drying at 60℃ for 16h, it was ground to obtain magnetic MnFe2O4.

[0035] (2) Preparation of glucose-modified magnetic metal oxide precursor: 1.6g of MnFe2O4 nanoparticles prepared in step (1) were ultrasonically dispersed in 160mL of distilled water, and 4.0g of glucose GC was added. After ultrasonic dispersion was continued and uniform, the mixture was transferred to a 200mL reactor and hydrothermally reacted at 200℃ for 12h. The product was initially enriched by a magnet, and after washing with ethanol and water several times, it was vacuum dried at 60℃ for 12h and then ground. The result was glucose-modified magnetic metal oxide precursor.

[0036] (3) Preparation of glucose-derived carbon-modified magnetic metal oxide (MnFe2O4@GC): The glucose-modified magnetic metal oxide precursor prepared in step (2) was placed in a tube furnace, the heating rate was controlled at 5℃ / min, and it was calcined at 500℃ for 4h. After grinding, MnFe2O4@GC was obtained.

[0037] Morphology and hysteresis loop of Example 1:

[0038] like Figure 1 As shown in (a) and (b), magnetic MnFe2O4 consists of nanoparticles with a slightly smaller average particle size and irregular shape, exhibiting agglomeration; while glucose carbon spheres are regular spheres with an average particle size of 20-100 nm. Figure 1 As shown in (c), after modification with glucose, magnetic MnFe2O4 is more uniformly dispersed on the carbon framework, and the aggregation phenomenon of magnetic MnFe2O4 is greatly improved. Because glucose undergoes a hydrothermal reaction, its original carbon sphere structure disappears, and a larger carbon framework gradually forms.

[0039] like Figure 2 As shown, compared to pure MnFe2O4, the saturation magnetization of the MnFe2O4@GC composite material is reduced because of the introduction of a non-magnetic glucose carbon support, with a magnetization of 21.21 emu / g. However, it is still sufficient to achieve catalyst-solution separation under an applied magnetic field. Figure 2 As shown in the illustration, applying a magnetic field to a homogeneous solution resulted in the MnFe2O4@GC composite material separating from the solution within 5 seconds, clarifying the solution. This result will contribute to the recycling of MnFe2O4@GC composite materials in practical applications.

[0040] Figure 3(a) is the high-resolution spectrum of C1s. The characteristic peaks with binding energies of 284.8 eV, 285.9 eV, and 288.9 eV are attributed to the CC / C=C, CO / C=O, and OC=O on the glucose carbon surface, respectively. The figure shows that the CO / C=O content on the MnFe2O4@GC surface decreased from 28.21% to 12.35% before and after the reaction, while the OC=O content increased from 5.28% to 21.75%. This indicates that CO / C=O may act as a potential active site, participating in the activation of PAA and being oxidized to OC=O, suggesting that a catalytic oxidation reaction may have occurred on the surface of the MnFe2O4@GC composite material. These oxygen-containing functional groups can serve as active sites for PAA activation and can also act as electron mediators to promote charge transfer and accelerate the catalytic reaction. Figure 3 In (b), two major Fe 2p3 / 2 peaks appear at binding energies of 710.8 eV and 713.7 eV, two satellite peaks appear at binding energies of 718.7 eV and 733.7 eV, and two major Fe 2p1 / 2 peaks appear at binding energies of 724.7 eV and 728.6 eV. The peaks at 710.8 eV and 724.7 eV are attributed to Fe. 3+ The oxides, with peaks at 713.7 eV and 728.6 eV, are attributed to Fe. 2+ The oxides, relative to the total Fe strength, accounted for 73.04% and 29.96%, respectively. After the catalytic reaction, Fe... 3+ and Fe 2+ The relative ratios were 67.01% and 32.99%, indicating that Fe... 3+ During the catalytic reaction, it is partially reduced to Fe. 2+ .also, Figure 3 In the (c) Mn2p spectrum, the Mn2p3 / 2 spectrum can be fitted to three peaks located at 640.7 eV, 642.4 eV, and 646.1 eV, which are attributed to Mn2p3 / 2. 2+ Mn 3+ And satellite peaks, Mn 2+ With Mn 3+ The peak area percentages were 65.23% and 34.77%, respectively. After the degradation reaction, Mn 2+ With Mn 3+ The peak area percentages changed to 61.9% and 38.1%, indicating that Mn was also present during the reaction. 3+ / Mn 2+ They can be converted between each other. The XPS spectrum of O 1s can be fitted to three peaks, such as... Figure 3 In the middle (d), 530.1 eV, 531.8 eV, and 533.5 eV are attributed to lattice oxygen (O) respectively. latt) Surface hydroxyl oxygen (·OH) and physically adsorbed H2O (O adsO in MnFe2O4 before the reaction latt , ·OH and O ads The relative contents were 51.48%, 31.94%, and 16.58%, respectively. After the catalytic reaction, O latt , ·OH and O ads The contents of Fe were changed to 48.32%, 37.12%, and 14.56%, respectively. The decrease in lattice oxygen content is generally attributed to the reduction in high-valence metal ions. In summary, Fe 2+ / Fe 3+ and Mn 3+ / Mn 2+ Redox pairs and glucose-carbon materials both participate in the activation of PAA.

[0041] Example 2

[0042] Effect of MnFe2O4@GC / PAA system on TC removal efficiency at different PAA concentrations:

[0043] The removal efficiency of different concentrations of PAA on TC was investigated under the conditions of pH 7, TC concentration of 10 mg / L, and MnFe2O4@GC catalyst dosage of 0.1 g / L. The results are shown in Table 1. The TC removal rate increased with increasing PAA concentration. As the PAA concentration increased from 50 μM to 200 μM, the TC removal rate increased from 65.80% to 98.10%. However, further increasing the PAA concentration to 250 μM did not significantly affect the degradation rate or final removal rate of TC by the MnFe2O4@GC / PAA system, indicating that the active sites on the surface of the MnFe2O4@GC catalyst had reached saturation at this point. Furthermore, excessive PAA may undergo self-degradation, resulting in waste of the oxidant.

[0044] Table 1. Effect of different PAA concentrations on TC removal efficiency

[0045]

[0046] Example 3

[0047] Effect of different MnFe2O4@GC dosages on TC removal efficiency of MnFe2O4@GC / PAA system:

[0048] The effect of different MnFe₂O₄@GC dosages on TC removal was investigated under the conditions of pH 7, TC concentration of 10 mg / L, and PAA concentration of 200 μM. The results are shown in Table 2. With increasing MnFe₂O₄@GC dosage, the TC removal rate increased. When the MnFe₂O₄@GC dosage increased from 0.04 g / L to 0.10 g / L, the TC removal rate increased from 75.72% to 98.10% after 30 min of reaction. Appropriately increasing the MnFe₂O₄@GC dosage can provide more PAA catalytic active sites, thereby promoting the formation of active species in the system. However, further increasing the MnFe₂O₄@GC dosage to 0.12 g / L did not significantly change the TC removal efficiency. This indicates that the rate-limiting step affecting the TC removal efficiency at this point is the PAA concentration.

[0049] Table 2. Effects of different MnFe2O4@GC dosages on TC removal efficiency

[0050]

[0051] Example 4

[0052] Effect of MnFe2O4@GC / PAA system on TC removal efficiency at different pH levels:

[0053] The removal efficiency of TC at different pH values ​​was investigated under the conditions of TC concentration of 10 mg / L, PAA concentration of 200 μM, and MnFe2O4@GC dosage of 0.1 g / L. The results are shown in Table 3. Under the conditions of initial pH of 3–9, the removal rates of TC by the MnFe2O4@GC / PAA system were 97.80% (pH=3), 93.41% (pH=5), 98.13% (pH=7), and 89.85% (pH=9), respectively. However, when the initial pH value was 11, the TC removal rate was only 69.37%, which was mainly attributed to the spontaneous decomposition of PAA and the formation of metal complexes under alkaline conditions.

[0054] Table 3. Effects of different pH values ​​on TC removal efficiency

[0055]

[0056] Example 5

[0057] The effect of the number of times MnFe2O4@GC is reused on TC removal efficiency:

[0058] To evaluate the catalytic stability of the MnFe2O4@GC catalyst in the TC removal reaction, the MnFe2O4@GC after the catalytic reaction was first collected using a magnet, then washed alternately with deionized water and ethanol, and finally vacuum dried at 60°C for later use. The effect of five reuses of MnFe2O4@GC on the TC removal efficiency is shown in Table 4. Even after the fifth reuse, the catalyst still exhibited good TC removal efficiency, with a removal rate of 90.81% after 30 min of reaction. This indicates that the repeatedly reused MnFe2O4@GC catalyst still has a good activation effect on PAA and can maintain high catalytic activity in the PAA oxidation TC removal system.

[0059] Table 4. Effect of catalyst reuse frequency on TC removal efficiency

[0060]

[0061] Example 6

[0062] The effect of different quenchers on the TC removal efficiency of the MnFe2O4@GC / PAA system:

[0063] To determine the contribution of reactive oxygen species in TC removal, free radical quenching experiments were conducted using four quenchers: tert-butanol (TBA), methanol (MeOH), 2,4-hexadiene (2,4-HD), and furfuryl alcohol (FFA). The results are shown in Table 5. At a dosage of 100 mM, the order of influence of the quenchers on TC removal efficiency was: 2,4-HD > MeOH > FFA > TBA, indicating that CH3C(O)OO· had the greatest impact on TC removal. 1 O2 and ·OH also participate in the removal of TC.

[0064] Table 5. Effects of different quenching agents on TC removal efficiency

[0065]

[0066] Example 7

[0067] Effects of MnFe2O4@GC / PAA system on TC removal efficiency under different anions and humic acids:

[0068] To verify the application of the MnFe2O4@GC / PAA system in actual water bodies, the effects of different anions and humic acids on TC removal efficiency were investigated, and the results are shown in Table 6. When 1 mM Cl is present in the MnFe2O4@GC / PAA system... - HCO3 2- SO4 2-When anions are present, the removal efficiency of TC is almost unaffected; however, when 5 mg / L of humic acid (HA) is present in the system, the removal efficiency of TC decreases slightly to 87.45%. This indicates that Cl... - HCO3 2- SO4 2- The presence of anions does not affect the removal of TC in the system, while HA may compete with TC for free radicals in the system, thus leading to a decrease in the removal rate of TC in the system.

[0069] Table 6. Effects of different anions and humic acids on TC removal efficiency.

[0070]

[0071] The above-described embodiments are preferred embodiments of the present invention, but the specific implementation of the present invention is not limited to the above-described embodiments. Any changes, modifications, simplifications, etc., made by those skilled in the art without departing from the spirit and principles of the present invention should be included within the scope of patent protection defined in the claims of the present invention.

Claims

1. A method for preparing a glucose-derived carbon-modified magnetic metal oxide catalyst, characterized in that, In the prepared MnFe2O4@GC composite catalyst, MnFe2O4 nanoparticles are uniformly supported on the surface of a glucose-derived carbon framework, with a saturation magnetization of 21.21 emu / g. Rapid catalyst separation is achieved through an external magnetic field. Simultaneously, the MnFe2O4@GC composite catalyst contains abundant oxygen-containing functional groups and Fe... 2+ / Fe 3+ and Mn 3+ / Mn 2+ Both redox couples contribute to the activation of PAA and the removal of TC; The preparation method includes the following steps: (1) Preparation of spinel manganese ferrite MnFe2O4: The metal salt was dissolved in ethylene glycol (EG). After it was completely dissolved, sodium acetate (NaAc) and polyethylene glycol (PEG) were added. After stirring thoroughly, the mixture was transferred to a reactor for aging. The product was initially enriched by a magnet and washed several times with ethanol and water. After vacuum drying, it was ground to obtain magnetic MnFe2O4 nanoparticles. The metal salts were FeCl3·6H2O and MnCl2·4H2O. (2) Preparation of glucose-modified magnetic metal oxide precursor: The magnetic MnFe2O4 nanoparticles obtained in step (1) were ultrasonically dispersed in deionized water, glucose GC was added, and after ultrasonic dispersion was continued to be uniform, the mixture was transferred to a reaction vessel for hydrothermal reaction; the product was initially enriched by a magnet, and after being washed several times with ethanol and water, it was dried under vacuum and then ground to obtain the glucose-modified magnetic metal oxide precursor. (3) Preparation of glucose-derived carbon-modified magnetic metal oxide (MnFe2O4@GC): The glucose-modified magnetic metal oxide precursor obtained in step (2) was placed in a tube furnace and calcined to obtain MnFe2O4@GC.

2. The preparation method according to claim 1, characterized in that, In step (1), the amounts of FeCl3·6H2O and MnCl2·4H2O added satisfy the following: the molar ratio of Fe:Mn is 5:1-2:1; the amount of EG is 80-100mL; and the amounts of NaAc and PEG are 4.8-7.2g and 1.5-3.0g, respectively.

3. The preparation method according to claim 1, characterized in that, In step (1), the aging temperature is 180-200℃ and the aging time is 10-12h; the vacuum drying temperature is 60-80℃ and the drying time is 16-20h.

4. The preparation method according to claim 1, characterized in that, In step (2), the mass ratio of magnetic MnFe2O4 nanoparticles to glucose is 1:5-2:5; the amount of distilled water used is 160-200mL.

5. The preparation method according to claim 1, characterized in that, In step (2), the hydrothermal reaction temperature is 180-200℃ and the hydrothermal reaction time is 12-14h; the vacuum drying temperature is 60-80℃ and the drying time is 16-20h.

6. The preparation method according to claim 1, characterized in that, In step (3), the heating rate of the tube furnace is 5-10℃ / min, the calcination temperature is 300-500℃, and the calcination time is 4-6h.

7. A glucose-derived carbon-modified magnetic metal oxide catalyst prepared by any one of claims 1-6.

8. The application of the catalyst according to claim 7 in the oxidative degradation of tetracycline TC by activated peracetic acid (PAA).

9. The application according to claim 8, characterized in that, The degradation reaction conditions were as follows: initial TC concentration 10 mg / L, PAA concentration 200 μM, catalyst dosage 0.1 g / L, initial pH 3.0-9.0, reaction time 30 min, and TC removal rate ≥97%.

10. The application according to claim 8 or 9, characterized in that, Even after being recycled 5 times, the catalyst still achieved a TC removal rate of ≥90%, demonstrating good stability and reusability.